2020
DOI: 10.1111/jcmm.15014
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of the KCa3.1 channel in mechanical stretch‐induced proliferation of rat bone marrow‐derived mesenchymal stem cells

Abstract: Mechanical stimulation is an important factor regulating mesenchymal stem cell (MSC) functions such as proliferation. The Ca2+‐activated K+ channel, KCa3.1, is critically engaged in MSC proliferation but its role in mechanical regulation of MSC proliferation remains unknown. Here, we examined the KCa3.1 channel expression and its role in rat bone marrow‐derived MSC (BMSC) proliferation in response to mechanical stretch. Application of mechanical stretch stimulated BMSC proliferation via promoting cell cycle pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…We and other groups have shown that the expression and activity of the IK Ca channel in VSMCs and other cell types such as endothelial cells and MSCs are sensitive to regulation by mechanical forces, such as shear stress or membrane stretch (Brakemeier et al, 2003; Hayabuchi et al, 2011; Jia et al, 2020; Takai et al, 2013). It is interesting to examine whether vascular stiffening‐related mechanical stimulation regulates the IK Ca channel expression and activity in VSMCs and thereby VSMC proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…We and other groups have shown that the expression and activity of the IK Ca channel in VSMCs and other cell types such as endothelial cells and MSCs are sensitive to regulation by mechanical forces, such as shear stress or membrane stretch (Brakemeier et al, 2003; Hayabuchi et al, 2011; Jia et al, 2020; Takai et al, 2013). It is interesting to examine whether vascular stiffening‐related mechanical stimulation regulates the IK Ca channel expression and activity in VSMCs and thereby VSMC proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, western blotting and RT-qPCR showed increased expression of osteogenic differentiation markers, including ALP, RUNX2, and Col1 in the mechanical stretch group (Figures 3(f) and 3(g) ). Ion channels residing in membrane structures of cells were previously reported to act as mechanical sensors [ 23 , 24 ], and intracellular calcium ion was recognized as a common second messenger responding to mechanical force [ 25 , 26 ]. Thus, we measured expression levels of IP 3 R, which is a calcium channel residing in the ER membrane [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple mechanical forces can drive the proliferation and differentiation of BMSCs. 15,16 According to several in vitro studies, [17][18][19] mechanical forces can also induce substantial changes in the osteoblast cytoskeleton, cell and nucleus morphology, and volume. FSS increased the expression of osteogenic genes in mesenchymal stem cells.…”
Section: Mechanosensitive Cellsmentioning
confidence: 99%